Perceptual grouping without awareness: superiority of Kanizsa triangle in breaking interocular suppression. - Lan Wang; Xuchu Weng; Sheng He (PLoS ONE, 2012)
Much information could be processed unconsciously. However, there is no direct evidence on whether perceptual grouping could occur without awareness. To answer this question, we investigated whether a Kanizsa triangle (an example of perceptual grouping) is processed differently from stimuli with the same local components but are ungrouped or weakly grouped. Specifically, using a suppression time paradigm we tested whether a Kanizsa triangle would emerge from interocular continuous flash suppression sooner than control stimuli. Results show a significant advantage of the Kanizsa triangle: the Kanizsa triangle emerged from suppression noise significantly faster than the control stimulus with the local Pacmen randomly rotated (t(9) = -2.78, p = 0.02); and also faster than the control stimulus with all Pacmen rotated 180° (t(11) = -3.20, p<0.01). Additional results demonstrated that the advantage of the grouped Kanizsa triangle could not be accounted for by the faster detection speed at the conscious level for the Kanizsa figures on a dynamic noise background. Our results indicate that certain properties supporting perceptual grouping could be processed in the absence of awareness.